Cosmic magnetic fields - Canary Islands Winter School of Astrophysics 2013 : La Laguna, Canary Islands); Sánchez Almeida, J. (Jorge); Martínez González, María Jesus (Cambridge, United Kingdom ; New York, NY : Cambridge University Press, 2018)
An introduction to cosmic magnetic fields on a range of astrophysical and cosmological scales for young researchers and graduate students.
Cover; Half title; Series; Title; Copyright; Contents; List of Contributors; List of Participants; Preface; Acknowledgments; 1 Astrophysical Magnetic Fields: Essentials; 2 Solar Magnetic Fields: History, Tragedy or Comedy?; 3 Stellar Magnetic Fields; 4 The Role of Magnetic Fields in AGN Activity and Feedback; 5 Magnetic Fields in Galaxies; 6 Primordial Magnetic Fields in the Early Universe and Cosmic Microwave Background Anisotropies.
Includes bibliographical references and index.
eBooks on EBSCOhost
Keywords: Cosmic magnetic fields -- Congresses; Champs magnétiques (Physique spatiale) -- Congrès.; SCIENCE -- Astronomy; Cosmic magnetic fields; Conference papers and proceedings